Ce(IV)-ion initiated grafting of 1, 3 galactomannan biopolymer with acrylonitrile. Issue 7 (2nd July 2020) - Sharma, Pradeep; Gupta, Sarika; Soni, P. L.; Kumar, Vineet
Abstract: Galactomannans based biopolymers are common constituents of ungerminated seeds of numerous leguminous plants present in endosperm of seeds. They are highly valuable in industries due to their ability to modify the flow behavior of aqueous solutions viz. thicken, suspend, gel, stabilize, swell and film formation. Consequently, they have diverse applications in food and non-food due to their biocompatibility, biodegradability, sustainability and abundance. Cassia occidentalis, an annual weed occurring throughout India is a rich source of seed galactomannans (∼30% endosperm). The gum derived from seed endosperm can be potentially utilized in a number of industries to replace the conventional expensive gums. However, the extracted gum has considerable disadvantages such as uncontrolled hydration, changes in viscosity during storage, pH-dependent solubility, lower shelf life etc, thereby, limiting their vast industrial applications. Intriguingly, these limitations can be overcome by functionalization of hydroxyl groups. Therefore, grafting onto C. occidentalis seed gum was carried out with acrylonitrile in presence of ceric ammonium nitrate under inert atmosphere. The reaction conditions were optimized by varying concentration of CAN, nitric acid, acrylonitrile, reaction temperature and time. The grafted gum was characterized using FTIR, TGA, DTG, X-Ray and SEM analysis.